Hydrothermally synthesized nanoparticles of zinc peroxide and their structural description - García Ruiz, Armando; Escobedo, A.; Aguilar Hernández, Alberto Issac; Esparza, Rodrigo; Pérez, R. (Universidad Autónoma de Puebla, 2011)
The aim of this work is to present some results of the synthesis of nanoparticles of zinc oxide by means of a hydrothermal method. Also, a description of the structural characteristics of these nanoparticles will be presented. The nanoparticles can be used as the supported active phase for photocatalytic applications, as has been recently published in the literature. The hydrothermal synthesis is based in dehydrated zinc acetate as the precursor using temperatures of 100ºC. The structural analysis of the obtained nanoparticles has been performed using X-ray diffraction techniques with a subsequent Rietveld refinement of the pattern. This allows obtaining refined values of the cell parameters and the aproximate crystallite sizes (10-20 nm) and also gives an insight on the morphology of the nanoparticle (truncated cube). Some high resolution electron microscope images are also presented and their structural results are compared with those obtained through the X-ray diffraction stuides.